COMPORTAMENTO GEOQUÍMICO DO URÂNIO NO MANTO DE INTEMPERISMO DA JAZIDA LARANJEIRAS, PROVÍNCIA URANÍFERA DE LAGOA REAL, BAHIA - Rocha, E. B.; Schmitt, J.-M.; Melfi, A. J. (Geochimica Brasiliensis, 2011)